Kemampuan Komunikasi Interpersonal terhadap Kinerja Pustakawan Dilingkup Kementerian Pertanian - Erriani Kristiyaningsih; Pudji Muljono; Eko Sri Mulyani (Jurnal Komunikasi Pembangunan, 2017)
Librarians at the Ministry of Agriculture are civil servants (PNS), who are appointed through a selection process whose duties and positions are governed in functional positions and credit figures based on ministerial regulations on the utilization of the state apparatus and the reform of the Indonesian bureaucracy. The librarian's profession as a civil servant is closely related to how they are able to communicate interpersonally and how it can support their performance as government employees. Therefore, the purpose of this study is to analyze the description of librarians of the ministry of agriculture, to analyze the relationship of librarian characteristics with the competence of interpersonal communication and to analyze the relation of competence of interpersonal communication and librarian performance. As well as analyzing the differences of interpersonal communication and the performance of expert librarians and skilled librarians. The research was conducted at library institution of Ministry of Agriculture with the number of respondents was 72 people. Data collection in the field was conducted during May 2017. The data obtained were processed using descriptive statistics, srearman ranks and chi-square to find relationships between variables. The majority of librarians judge that the competence of their interpersonal communication is in the category of both skilled librarians and expert librarians. Relationship characteristic with interpersonal communication occurs only on indicator of gender relationship to supportiveness and positiveness, formal and norformal education level to Positiveness. Performance has a relationship with interpersonal communication based on credit score only on indicator supportiveness. Overall performance indicators of work behavior assessment are significantly related to interpersonal communication. Empathy, Positiveness and supportiveness of expert and skilled librarians have real differences. While the performance of expert and skilled librarians has no real difference.